REVISITING ERROR ANALYSIS–THE CASE OF BANGLADESHI EFL STUDENT - Rahnuma, Naureen (PEOPLE: International Journal of Social Sciences, 2015)
Errors are ubiquitous when it comes to language learning. But the question remains, do errors signpost both progress and regress? This article attempts to scrutinize the ways Error Analysis (EA) can be re-established as a valuable tool for gathering information about how much a Bangladeshi adult EFL learner has learnt after a three month long Academic English course. Thus, a detailed EA carried out on two written texts present much crucial information about the learner’s language development - from lexical deficiency to shortfalls in grammatical knowledge and even on the sociolinguistic or discourse level. The paper concludes with the limitations as well as pedagogical implications of the study.